Evaluasi Biaya Perangkat Lunak Menggunakan Metode Fuzzy Use Case Point: Indonesia - Rika Priyanti Manik; Andi Reza Perdanakusuma; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Software cost estimation is a very important aspect in information technology project for budgeting. Software house produces various software continously in limited time and cost. Therefore, a good budgeting is required by doing cost estimation. Software house PT. Sekawan Media Informatika dan CV. Profile Image at this research, still do not have a standard format to do cost estimation. Cost estimation in this research utilizes Fuzzy Use Case Point method. Cost estimation is obtained after getting time estimation. Then, the estimated cost and time are allocated to each phase that occurs in the software development (in this research, SIPAS and SMTPX), thus it provides suggestion for scheduling the development of software SIPAS and SMTPX. Fuzzy Use Case Point method, that is used to get the cost estimation, evaluated by using 2 software development projects that had been completed. At the end of this research, evaluation of cost estimation for software development is conducted, by comparing the cost estimation result which is gotten by using Fuzzy Use Case Point method with software house's actual cost allocation. The evaluation result from this research is useful to give such as consideration for software house to allocate cost for software development through estimation method Fuzzy Use Case Point.